Impact of ambient temperatures on Alzheimer's disease and other dementia mortality among elderly patients aged 60 years and older in China - Rui Zhang; Lu Sun; Ai-Nan Jia; Si-Yuan Wu; Yu Wang; Song-Wang Wang; Qing Guo; Yu-Jie Meng; Juan Liang; Wan Huang; Yong-Hong Li; Jing Wu (Advances in Climate Change Research)
China has a large number of patients with Alzheimer's disease (AD) and types of other dementia, which places a heavy burden on the public health and medical systems. As global climate change results in more frequent extreme weather events, and there is a current lack of understanding regarding the impact of non-optimal temperatures, especially cold, on AD and other dementia mortality, the study aimed to identify patterns of temperature sensitivity in order to inform targeted public health strategies. The records of 399,214 decedents aged 60 years and older who died due to AD or other dementias from 2013 to 2020 were obtained from the China Cause of Death Reporting System. Using an individual-level time-stratified case-crossover study design, the relationships between ambient temperatures and AD and other dementia mortality were quantified using conditional logistic regression combined with the distributed lag nonlinear model. In addition, the attributable fractions (AFs) of mortality due to non-optimal ambient temperatures were calculated. The study found that both low and high non-optimal temperatures were associated with an increased risk of death from AD and other dementias, with an inverted J-shaped exposure–response curve. Moreover, the AFs of mortality due to full, low and high non-optimal temperatures with lag0–14 were 5.81% (95% empirical confidence interval [eCI]: 4.89%, 6.72%), 5.24% (95% eCI: 4.15%, 6.27%) and 0.58% (95% eCI: 0.27%, 0.90%), respectively. Importantly, AFs varied across administrative regions, influenced by factors such as climate, geography, sociodemographic characteristics and socioeconomic factors. These findings can inform clinical and public health practices to reduce the mortality burden due to non-optimal temperatures on elderly populations with AD and other dementias.